2021
DOI: 10.3390/catal11060727
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Laccase-Mediated Oxidation of New Condensed 1,4-Dihydropyridine Derivatives

Abstract: We describe herein the synthesis and laccase mediated oxidation of six novel 1,4-dihydropyridine (DHP)-based hexahydroquinolines (DHP1-DHP3) and decahydroacridines (DHP4-DHP6). We employed different laccase enzymes with varying redox potential to convert DHP1-DHP3 and DHP4-DHP6 to the corresponding pyridine-containing tetrahydroquinoline and octahydroacridine derivatives, respectively. Intensively coloured products were detected in all biocatalytic reactions using laccase from Trametes versicolor (TvLacc), pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The exceptions were the strains of the species Trametes hirsuta, which turned out to be the only biocatalysts that showed activity towards substrate 1a among all the tested strains (Table 4). The literature data has indicated that strains of the Trametes genus are well-known for having alkene cleaving properties in a wide range of chemical compounds [12][13][14][15][16][17][18][19][20][21]. In particular, very promising results were obtained during the process using T. hirsuta Th2_2 as a biocatalyst, where 38% of piperonal (1b) was obtained after 14 days of biotransformation.…”
Section: The Influence Of Carbon and Nitrogen Source On Biotransforma...mentioning
confidence: 99%
“…The exceptions were the strains of the species Trametes hirsuta, which turned out to be the only biocatalysts that showed activity towards substrate 1a among all the tested strains (Table 4). The literature data has indicated that strains of the Trametes genus are well-known for having alkene cleaving properties in a wide range of chemical compounds [12][13][14][15][16][17][18][19][20][21]. In particular, very promising results were obtained during the process using T. hirsuta Th2_2 as a biocatalyst, where 38% of piperonal (1b) was obtained after 14 days of biotransformation.…”
Section: The Influence Of Carbon and Nitrogen Source On Biotransforma...mentioning
confidence: 99%
“…The 1 H and 13 C NMR analyses were carried out using a Bruker AC 250-Magnet (2005, Bruker Center AXS, Karlsruhe, Germany) equipment, operating at 250 MHz. The samples were prepared in 500 µL of CDCl 3 containing, approximately, 5 mg of sample.…”
Section: Nmr Studiesmentioning
confidence: 99%
“…These compounds find extensive applications in pharmacology, agrochemistry, organic synthesis, and industry. Despite the wide range of oxidizing agents available for this process, from inorganic salts, solid supports, microwaves, ultrasound, enzymes, UV-Vis, organo-inorganic molecular systems to Cytochrome P-450 [9][10][11][12][13][14][15][16][17], the oxidative aromatization of dihydropyridines presents real issues. These include the steric constrain and reactivity of functional groups in the molecule, sensitivity to various reagents and reaction conditions, and the formation of secondary products.…”
Section: Introductionmentioning
confidence: 99%